«¡Gózate, Cataluña!»: La celebración en Barcelona de la recuperación de Carlos II en 1696. - TORRENTE, ÁLVARO (Scripta, 2018)
1696 was a difficult year in Spanish history owing to the health problems of a monarch without an heir, and was perceived as particularly troublesome in Catalonia due to the French invasion during the Nine Years' War. The recovery of the King's health in October prompted spirited celebrations, especially in Barcelona, where the four main institutions --Ciudad, Diputación, Brazo Militar and Lonja del Mar-- organized a series of religious festivities that included the singing of lavish polycoral villancicos whose lyrics are closer to be political pamphlets rather than spiritual poems. This article analyses the circumstances of the celebrations, the politico-doctrinal messages of the villancicos and the characteristics of the surviving scores, two of them attributed to Francisco Valls, that would position him as the leading composer in the Principado for the coming decades.